2013
DOI: 10.1371/journal.pone.0059580
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Spontaneous Recovery of Fear by mGluR5 after Prolonged Extinction Training

Abstract: Fear behavior is vital for survival and involves learning contingent associations of non-threatening cues with aversive stimuli. In contrast, excessive levels of fear can be maladaptive and lead to anxiety disorders. Generally, extensive sessions of extinction training correlates with reduced spontaneous recovery. The molecular mechanisms underlying the long-term inhibition of fear recovery following repeated extinction training are not fully understood. Here we show that in rats, prolonged extinction training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…In contrast, the erasure mechanism has been supported by previous studies using both single- and multiple-session extinction training (Rescorla and Wagner, 1972; Lin et al, 2003; Kim et al, 2007; Dalton et al, 2008; Mao et al, 2013). These findings provide a hint that the inhibition mechanism is involved primarily in the early phase of extinction training.…”
Section: Introductionmentioning
confidence: 69%
“…In contrast, the erasure mechanism has been supported by previous studies using both single- and multiple-session extinction training (Rescorla and Wagner, 1972; Lin et al, 2003; Kim et al, 2007; Dalton et al, 2008; Mao et al, 2013). These findings provide a hint that the inhibition mechanism is involved primarily in the early phase of extinction training.…”
Section: Introductionmentioning
confidence: 69%
“…How mGluR5 regulates the extinction of fear and spatial memory remains largely unknown. It has been demonstrated that repeated extinction sessions over days trigger up-regulation of mGluR5 expression in the hippocampus (Riedel, Casabona, Platt, Macphail, and Nicoletti, 2000), which may lead to reduction in subsequent recall or spontaneous recovery of fear (Mao, Chang, Wu, Orejarena, Manzoni, and Gean, 2013). At the cellular level, it is suggested that mGluR5 activity supports the extinction-induced changes in AMPA receptor/NMDA receptor ratio and intrinsic excitability in prefrontal cortex (Sepulveda-Orengo, Lopez, Soler-Cedeno, and Porter, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Rodent models of fear learning (ie, fear conditioning) and fear extinction learning have enriched our understanding of genes and neural circuits involved in the expression of GAD and PTSD symptoms (reviewed in Fenster et al 1 ). [12][13][14][15][16] In humans, extinction learning is a main component of exposure therapy, which is often used in the treatment of PTSD. 3 Following one or more CS-US pairings, rodents will typically display a fearful response to the CS alone (conditioned response).…”
Section: Introductionmentioning
confidence: 99%
“…Extinction learning involves both forming new associations [4][5][6][7][8][9][10][11] and degradation of the originally learned CS-US pairing. [12][13][14][15][16] In humans, extinction learning is a main component of exposure therapy, which is often used in the treatment of PTSD.…”
Section: Introductionmentioning
confidence: 99%